Performance Analysis of a Direct Absorption Solar Collector using Different Nanofluids: Effect of Physical Parameters - Parvin, Salma; Islam, Abrar; Nahar, Afroza (GANIT: Journal of Bangladesh Mathematical Society, 2022)
Nanofluids have been used in direct absorption solar collectors (DASC) to enhance their performance, wherein contribution of entropy generation plays a decisive role. Among other factors, entropy generation is influenced including physical structure of the system and operation conditions. In this article, heat transfer and efficiency of a nanofluid based DASC considering the entropy generation has been performed for various physical alterations and operating conditions. Working nanofluids are chosen to Cu-water nanofluid, Al2O3-waternanofluid, TiO2-waternanofluid and water is chosen as base fluid. Solar irradiation value for the current analysis is considered 225W/m2 from the annual average solar irradiance range (215 W/m2 in the north-west to 235 W/m2 in the south-west per day) in Bangladesh according to UNDP report. Governing equations consisting of Navier–Stokes and energy equations are solved by Penalty finite element method with Galerkins weighted residual approach. Impact of parameters nanoparticle concentration and thickness of flow on isotherms, average output temperature, the average Nusselt number, collector efficiency, average entropy generation and Bejan number are discussed for all considered fluids. Results reveal that DASC system exhibits efficacy in heat transfer using 2% Cu nanoparticles under 225W/m2 irradiance, 0.015 kg/s mass flow rate and 0.015 m flow thickness. The outcomes will be supportive in designing DASC to attain improved heat transfer performance considering entropy generation. GANITJ. Bangladesh Math. Soc.41.2 (2021) 18-33